Monte Carlo study of multibarrier heterostructure switch - Reklaitis, A.; Grigaliūnaitė, G. (Nonlinear Analysis: Modelling and Control, 1998)
A multibarrier heterostructure GaAs/AlAs current switching diode has been investigated by Monte Carlo method. The switching phenomenon is based on electron tunnelling and thermoemission from the GaAs wells to the AlAs barriers, electron drift across the thin AlAs barriers followed by a subsequent impact ionisation in the undoped GaAs layers. The calculated switching voltage is close to 100 V for the diode involving four AlAs barriers at 300 K lattice temperature. The estimated switching time is in the order of 10 ps.
Keywords: none